Expression of Transforming Growth Factor Beta 1 in Lung Tissue during Cardiopulmonary Bypass-Induced Lung Injury in Dogs - Wang, Xiaofei; Qu, Xianfeng; Zhong, Qiaosheng; Li, Qianyu; Wang, Dongguo (The Thoracic and Cardiovascular Surgeon, 2013)
Background Cardiopulmonary bypass (CPB) is a necessary technique for cardiac surgery and usually induces acute lung injury. Transforming growth factor β1 (TGFβ1) has been found to play a crucial role in the pathogenesis of inflammatory diseases; however, whether TGFβ1 is also involved in CPB-induced lung injury has yet to be determined. Therefore, we aimed to investigate the TGFβ1 expression in the lungs of dogs after CPB.Methods A total of 36 healthy mongrel dogs were randomly assigned to control and CPB groups. Six dogs in each group were killed before, 30 min after the operation, and 60 min after the operation (T0, T1, and T2). Lung injury was evaluated by hematoxylin and eosin staining. Respiratory index (RI), oxygenation index (OI), malondialdehyde (MDA) content in the lung, and pulmonary permeability index (PPI) were determined at each time point. TGFβ1 expression was determined using real-time reverse transcription polymerase chain reaction and immunohistochemistry.Results There was a serious lung injury observed after CPB in dogs. RI increased and OI decreased in the dogs after CPB. The MDA content significantly increased after CPB; however, no significant change of MDA occurred in the control group. A significant increase of PPI was detected in CPB group at the T1 and T2 time points compared with that at the T0 time point. TGFβ1 expression in the lung was increased after CPB on both the mRNA and protein levels. Positive correlations between TGFβ1 mRNA level and MDA (r = 0.867, p < 0.01) and between TGFβ1 mRNA and PPI (r = 0.821, p < 0.01) were detected by linear correlation.Conclusion The upregulation of TGFβ1 expression plays an important role in the development and progression of CPB-induced acute lung injury.
Keywords: cardiopulmonary bypass; lung injury; transforming growth factor β; dog